SINESTESIA BAHASA BATAK TOBA - David Samosir; Mangatur Sinaga; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Sinestesia is a change of meaning caused by the exchange of responses between two different senses. The purpose of this study is to describe the synestheses of Batak Toba language. This research type is qualitative research. In this research, writer use descriptive method. Descriptive method is a method done with the steps as follows: data collection, classify, analyze, and make conclusions to get the picture object. This research uses data that is qualitative. The data taken is the language corpus of the Toba Batak language songs and daily conversation of the Batak Toba community. The data source of this research are 1) Batak Toba songs and 2) daily conversation of Batak Toba community. To collect research data from the Toba Batak language conversation, the author listened to the speech of Batak Toba community in Buluduri Village, North Sumatera and Pekanbaru. Talks containing synesthesia are then recorded or transcribed. The research data collecting from Batak Toba song writer do by transcribing song lyrics to be analyzed according to problem formulation in research. The result of the research was found 71 data included in the change of taste perception to the listener sensation there are 18 data, the change of taste perception to the sense of view there are 9 data, the change of sensory perception to the listener sensation there are 13 data, the change of sensory response of listener to the sense of view there 3 data, changes in sensory response of the listener to the senses of taste There are 2 data, the change of sensory perception to the sense of view there are 5 data, the change of sensory perception to the senses listener there are 13 data, the change of senses listener to the sense of taste there are 3 data, kisser to the senses listener there are 3 data, and the change of sensory perception to the senses of smell there are 2 data.Keywords: Sinestesia, Batak Toba language